Фразеологізми з числовим компонентом в українській та польській мовах - Jeż, Magdalena (Acta Polono-Ruthenica, 2018)
The article deals with the problem o f Ukrainian and Polish phraseology with the numeral component. The main intention o f this article is to analyze semantic peculiarities o f phraseological units with this component in both Slavic languages. The groups o f lexical equivalency o f Polish and Ukrainian phraseological units with numeral component are fixed. The phraseological variants and synonymy are explored.